Violence behind the Closed Door: Depression, Suicidal Ideation and Future Concerns Among its Spectators - Khurshid, Saba; Toor, Hafsa Khalil; Pervaiz, Farrah (Pakistan Armed Forces Medical Journal, 2023)
Objective: To determine the depression, suicidal ideation, and future concerns among domestic violence spectators. Study Design: Exploratory study design. Place and Duration of Study: Shelter Homes and Community Centres, in Rawalpindi/Islamabad Pakistan, from Aug to Nov 2022. Methodology: In-depth interviews with 30 participants aged 12 to 17 years were conducted to assess the future apprehensions and worries of domestic violence spectators. Interviews were recorded and transcribed for thematic analysis. Transcribed data were critically reviewed, and themes were identified. Inter-rater reliability was calculated with the help of Cohen Kappa and was found to be in substantial agreement. Results: The study findings identified major themes related to psychological issues and future apprehensions among participants who witnessed domestic violence. Maladaptive relationships with parents and intensification of social problems such as isolation, self-harm, social withdrawal, suicidal ideation, difficulty in making friends, and apprehensions about the future relationship with a partner were also perceived as serious future concerns among domestic violence spectators. Conclusion: Domestic violence takes a toll on the mental and physical well-being of not only its victims but also its spectators. Early detection and prevention of violent exposure are essential to mitigate its long-term psychological impact.